PHILOSOPHICAL FOUNDATIONS FOR RESEARCH AND DEVELOPMENT OF SHARIA ECONOMIC LAW METHODOLOGY:: An Integrative Approach to Ontology, Epistemology, and Axiology - Suaidi, Suaidi; Nasrudin, Muhamad (Institut Agama Islam Negeri Metro, 2025)
This study examines the philosophical dimensions in the development of Sharia economic law methodology by highlighting three main aspects: ontological, epistemological, and axiological. The purpose of this research is to formulate a methodological framework capable of integrating the normative Islamic sources based on divine revelation with scientific rationality and empirical perspectives within the discipline of economics. Methodologically, this normative-legal study employs a qualitative approach through a philosophical–integrative library research method. This approach involves a critical analysis of classical and contemporary literature on Islamic law, economic theory, and the philosophy of science, to formulate the relationship between spiritual and material realities, as well as between transcendental values and the empirical realities of the economy. Through this approach, the research is not only descriptive of the methodology of Sharia economic law but also constructive in formulating the direction for developing an adaptive Sharia economic law methodology in response to modern socio-economic dynamics. The findings show that, ontologically, Sharia economic law is rooted in the integration of spiritual and material realities; epistemologically, it combines revelation, rationality, and empirical understanding as the foundation of legal knowledge; and axiologically, it emphasizes justice, balance, and public benefit (maṣlaḥah) as its normative orientation. Thus, this study contributes to strengthening the philosophical foundation while providing a conceptual direction for the development of Sharia economic law methodology that is holistic, adaptive, and grounded in Islamic ethical values consistent with the maqāṣid al-sharī‘ah, ensuring its continued relevance to contemporary global economic challenges.